Estimated time spent on preventive services by primary care physicians - Gradison Margaret; Yarnall Kimberly SH; Krause Katrina M; Pollak Kathryn I; Michener J Lloyd; Østbye Truls (BMC, 2008)
Abstract Background Delivery of preventive health services in primary care is lacking. One of the main barriers is lack of time. We estimated the amount of time primary care physicians spend on important preventive health services. Methods We analyzed a large dataset of primary care (family and internal medicine) visits using the National Ambulatory Medical Care Survey (2001-4); analyses were conducted 2007-8. Multiple linear regression was used to estimate the amount of time spent delivering each preventive service, controlling for demographic covariates. Results Preventive visits were longer than chronic care visits (M = 22.4, SD = 11.8, M = 18.9, SD = 9.2, respectively). New patients required more time from physicians. Services on which physicians spent relatively more time were prostate specific antigen (PSA), cholesterol, Papanicolaou (Pap) smear, mammography, exercise counseling, and blood pressure. Physicians spent less time than recommended on two "A" rated ("good evidence") services, tobacco cessation and Pap smear (in preventive visits), and one "B" rated ("at least fair evidence") service, nutrition counseling. Physicians spent substantial time on two services that have an "I" rating ("inconclusive evidence of effectiveness"), PSA and exercise counseling. Conclusion Even with limited time, physicians address many of the "A" rated services adequately. However, they may be spending less time than recommended for important services, especially smoking cessation, Pap smear, and nutrition counseling. Future research is needed to understand how physicians decide how to allocate their time to address preventive health.